2020
DOI: 10.2499/p15738coll2.133762_11
|View full text |Cite
|
Sign up to set email alerts
|

Lockdowns are protecting China’s rural families from COVID-19, but the economic burden is heavy

Abstract: In response to the COVID-19 outbreak in December 2019, China implemented a nationwide travel blockade and quarantine policy that required all public spaces, businesses, and schools to shut their doors until further notice and placed restrictions on individuals leaving their homes or traveling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…However, most rural workers are blue-collar and cannot work from home, and then they cannot get paid. It is reported that almost every person in rural areas had stopped working—either working in a city as a migrant laborer or in their local counties as an off-farm worker [ 3 ]. The closure of workplaces and the transportation restrictions force farmers to stop working.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most rural workers are blue-collar and cannot work from home, and then they cannot get paid. It is reported that almost every person in rural areas had stopped working—either working in a city as a migrant laborer or in their local counties as an off-farm worker [ 3 ]. The closure of workplaces and the transportation restrictions force farmers to stop working.…”
Section: Resultsmentioning
confidence: 99%
“…The sharp decline in employment decrease migrated farmers' income since that in the urban area of China, workers can still get a salary if they do not work during the quarantine as required by China's state council; however, most rural workers cannot get paid because of their meager social safety net. It is estimated that farmers will lose around $100 billion in wages after one month of quarantine, which is more than the total global economic loss of SARS [ 3 ]. Thirdly, due to quarantine and transportation restrictions, farmers' local agricultural activities cannot continue, and the agricultural products cannot be sold, which indicates a radical decline in agricultural income for the entire year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Rozelle et al . (2020) find that rural families suffering from income losses cut back significantly on nutrition, buying more grains and staples in bulk at low cost instead of more expensive goods like meat and produce. Hirvonen et al .…”
Section: Why the Poor Are Most Affectedmentioning
confidence: 99%
“…Poor people who have to travel for work are the hardest‐hit by Covid‐19 restrictions. Studies show large negative effects for migrant workers in several categories: rural‐urban (as in China – see Rozelle et al., 2020), international (as in Egypt – see Breisinger et al., 2020) or rural‐rural (as in India, where landless workers travel to work in seasonal jobs such as harvesting). Rozelle et al .…”
Section: Why the Poor Are Most Affectedmentioning
confidence: 99%